2015
DOI: 10.3390/ijerph120605886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Electromagnetic Interference with Active Cardiovascular Implantable Electronic Devices (CIEDs) Caused by the Qi A13 Design Wireless Charging Board

Abstract: Electromagnetic interference is a concern for people wearing cardiovascular implantable electronic devices (CIEDs). The aim of this study was to assess the electromagnetic compatibility between CIEDs and the magnetic field of a common wireless charging technology. To do so the voltage induced in CIEDs by Qi A13 design magnetic fields were measured and compared with the performance limits set by ISO 14117. In order to carry this out a measuring circuit was developed which can be connected with unipolar or bipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…1.26 µT). Gustrau et al , 61 Seckler et al , 58 and Mattei et al 59 found a dependence of the induced voltage on lead configuration.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…1.26 µT). Gustrau et al , 61 Seckler et al , 58 and Mattei et al 59 found a dependence of the induced voltage on lead configuration.…”
Section: Resultsmentioning
confidence: 95%
“…Seckler et al 58 investigated a WPT system and compared the data with a standardized exposure set-up using Helmholtz coils (111 kHz, both systems). Under the standardized exposure condition the performance limit (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WPC developed an open interface standard that defines wireless power transfer using inductive charging. Also, recent study regarding wireless power transmission for implantable devices revealed that the induced magnetic field using Qi wireless charging was well below the limits set by ISO 14117 evaluating the electromagnetic compatibility (EMC) of active implantable cardiovascular devices [ 40 ].…”
Section: Methodsmentioning
confidence: 99%